Correlation between lenticulostriate arteries and white matter microstructure changes in patients with cerebral small vessel disease - Zhang, Yukun; Chang, Peipei; Liu, Na; Jiang, Yuhan; Chu, Ying; Du, Wei; Lin, Liangjie; Gao, Bingbing; Li, Yuan; Qu, Mingrui; Yang, Chao; Miao, YanWei (Frontiers in Neuroscience, 2023)
To explore the correlation between the number of lenticulostriate arteries (LSAs) and the white matter features in cerebral small vessel diseases (CSVD) by 3T magnetic resonance imaging (MRI). Seventy-one patients with diagnoses of CSVD were prospectively enrolled to undergo 3T MRI examination, including high-resolution vascular wall imaging (VWI) and diffusion tensor imaging (DTI). The LSAs were observed and counted on VWI, and the patients were divided into three groups according to the LSA counts. The presence of white matter hyperintensities (WMHs), lacunes, cerebral microbleeds (CMBs), and enlarged perivascular spaces (EPVS) was assessed in each patient, and a composite CSVD score was calculated. Periventricular and deep white matter hyperintensity (PVWMH, DWMH) volume ratios were obtained based on automatic segmentation. Fractional anisotropy (FA) and mean diffusivity (MD) were processed by using tract-based spatial statistics (TBSS) analysis. These parameters were compared among the three groups. Correlations between the LSA counts and white matter features were also analyzed. There were differences in WMHs (P = 0.001), CMBs (P < 0.001), EPVS (P = 0.017), composite CSVD scores (P < 0.001), PVWMH volume ratios (P = 0.001), DWMH volume ratios (P < 0.001), global FA (P = 0.001), and global MD (P = 0.002) among the three groups. There were correlations between the LSA counts and WMHs (r = −0.45, P < 0.001), CMBs (r = −0.44, P < 0.001), EPVS (r = −0.28, P = 0.020), the composite CSVD score (r = −0.52, P < 0.001), DWMH volume ratio (r = −0.47, P < 0.001), PWMH volume ratio (r = −0.34, P = 0.004), global FA (r = 0.36, P = 0.002), and global MD (r = −0.33, P = 0.005). Diabetes mellitus (OR 3.36, 95% CI 1.06–10.63; P = 0.039) and increased DWMH volume ratios (OR 1.04, 95% CI 1.00–1.08; P = 0.048) were independent risk factors for a decrease in LSA counts. TBSS analysis showed differences among the three groups in global FA and MD after adjusting for age and sex (P < 0.05). The LSA counts was associated with white matter microstructure changes in CSVD and has the potential to represent the extent of subcortical microvascular damage in CSVD patients.